(untitled) (Balneo and PRM Research Journal, 2024)
We aim was to present a case of severe osteoporosis with concern to an adult female who was under specific medication against the condition while she experienced inexplicable weight loss in association with an incidental fracture inconsistent with DXA changes. Challenges of the case management and decision making are further on explained. Real-life-medicine poses multiple issues that require an individual decision while respecting the standard protocols. That is why a generalized decision is rather impractical. Here we introduce the clinical case of a lady in her late 60s with a known 6-year history of osteoporosis that required several difficult decisions along surveillance: at first, zoledronic acid represented an available solution, yet after one year, BMD decreased and adjustment was done by initiating a second sequence according to the teriparatide protocol. DXA-BMD, as well as the spectrum of bone turnover markers, qualified the patient as responsive and she further continued with oral bisphosphonates while being monitored via telemedicine amid COVID-19 pandemic. After 24 more months, a second decision of zoledronic acid was done, despite prior partial response, but digestive complains restricted the oral administration of anti-osteoporotic drugs. After one more year, denosumab was initiated and consecutive follow-up is essential. At this point, another challenging aspect was revealed: the discordance between DXA – based scores increase and the presence of an incidental fracture. A supplementary investigation was considered useful (Tc- whole body scintigraphy) noting the clinical presentation with local pain, dysfunctionality, and mild weight loss that also required rehabilitation management. Keywords: DXA, osteoporotic fracture, rehabilitation, pain, surgery, anti-resorptive, teriparatide, zoledronate, weight loss